2000
DOI: 10.1074/jbc.m005450200
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase Facilitates Platelet-derived Growth Factor-BB-stimulated ERK2 Activation Required for Chemotaxis Migration of Vascular Smooth Muscle Cells

Abstract: Several vascular diseases result from neointima formation, a process that is characterized by the accumulation of vascular smooth muscle cells (SMCs) 1 and extracellular matrix (ECM) proteins in the intima of blood vessels (1). Neointima formation is triggered upon damage to the endothelial lining by the local release of chemotactic cytokines or growth factors (2) and by increased production of ECM proteins (3). Because combinations of these factors can stimulate cell division, it was originally hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 42 publications
4
92
3
Order By: Relevance
“…We therefore, speculate that FAK may also be an upstream factor responsible for phosphorylation of cytoskeletal components after SMC exposure to elastin peptides. It has also been shown that FAK facilitates ERK2 activation in vascular smooth muscle cells stimulated by PDGF-BB (85) and that ERK2 activation can be connected to an increased activityofmyosinlightchainkinase (79).Becauseelastinpeptidedependent tyrosine phosphorylation of FAK was also abolished in cells preincubated with lactose, pertussis toxin, and nisoldipine, we conclude that its activation comprises a downstream event of the EBP-dependent stimulation of G protein and may require influx of Ca 2ϩ . Because an up-to-date specific inhibitor of FAK has not been described and we did not attempt the FAK knock-out transfection of arterial SMC, we can only guess (Fig.…”
Section: Figmentioning
confidence: 52%
“…We therefore, speculate that FAK may also be an upstream factor responsible for phosphorylation of cytoskeletal components after SMC exposure to elastin peptides. It has also been shown that FAK facilitates ERK2 activation in vascular smooth muscle cells stimulated by PDGF-BB (85) and that ERK2 activation can be connected to an increased activityofmyosinlightchainkinase (79).Becauseelastinpeptidedependent tyrosine phosphorylation of FAK was also abolished in cells preincubated with lactose, pertussis toxin, and nisoldipine, we conclude that its activation comprises a downstream event of the EBP-dependent stimulation of G protein and may require influx of Ca 2ϩ . Because an up-to-date specific inhibitor of FAK has not been described and we did not attempt the FAK knock-out transfection of arterial SMC, we can only guess (Fig.…”
Section: Figmentioning
confidence: 52%
“…Phosphorylation State of ERK-1/2 Induced by S1P and SF/HGF Since ERK-1/2 plays an important role in regulating cell motility [Howe et al, 2002], and recent evidence supports a role for anchoragedependent activation of ERK by growth factors in regulating chemotactic migration [Cho and Klemke, 2000;Hauck et al, 2000], we examined whether Dp could have an effect on the induction of ERK-1/2 phosphorylation by the two most potent stimulators of glioblastoma cell migration, S1P and SF/HGF. Quiescent U-87 cells were incubated in serum-free medium in the presence or absence of Dp for 24 h and cells were then stimulated with 1 mM S1P or 50 ng/ml SF/HGF.…”
Section: Delphinidin Does Not Affect the Tyrosinementioning
confidence: 99%
“…Constructs encoding for a dominant negative truncated form of FAK, termed FRNK, and an inactive FRNK (FRNK L1034S) deficient in focal adhesion localization were transfected into BAE cells (50,51). In addition, a FAK construct containing a mutated Tyr 397 residue, which can incorporate into focal adhesions but not become activated, was also employed.…”
Section: Fak Is Required For Tsp1/hep I-induced Focal Adhesionmentioning
confidence: 99%